(untitled) (Colombia Medica, 1992)
An explanation of the risk conditions under which language acquisition and language development disorders could appear is described and given. A language disorder’s impact on a baby is discussed, placing primary emphasis on human consequences. Language acquisition is a process of tight relationships among the biological and communicative aspects. Also, risk and vulnerability are organic factors that are considered causes of language disorders. Finally, speech-and-language intervention is considered an alternative to assure the baby at risk the right to well-being in terms of communication.